Thermal conductive sheet
Patent Information
- Application Number
- JP2025059897
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2025-03-31
- Publication Date
- 2026-10-14
AI Technical Summary
【0014】 本発明によれば、低圧圧縮時の熱抵抗が低い熱伝導シートを提供することができる。
Smart Images

Figure 2026166746000001_ABST
Abstract
Description
[Technical Field]
[0001] This invention relates to a thermal conductive sheet. [Background technology]
[0002] In recent years, electronic components such as power semiconductors (IGBT modules, etc.) and integrated circuit (IC) chips have been generating increasing amounts of heat as their performance has improved. As a result, electronic devices using these components require measures to prevent functional failures caused by the temperature rise of the electronic components.
[0003] To prevent malfunctions caused by temperature increases in electronic components, a common method is to promote heat dissipation by attaching heat sinks, heat dissipation plates, or heat fins made of metal to the heat-generating elements of electronic components. When using heat sinks, a sheet-like material with high thermal conductivity (thermal conductive sheet) is used as an intermediary to efficiently transfer heat from the heat-generating element to the heat sink. A predetermined pressure is then applied to this thermal conductive sheet to ensure close contact between the heat-generating element and the heat sink.
[0004] Conventionally, thermal conductive sheets have been developed that possess both tackiness and strength, as well as excellent thermal conductivity. For example, Patent Document 1 proposes a thermal conductive sheet comprising a composition containing a thermally conductive inorganic material and an organic polymer compound, wherein the inorganic material is oriented at an angle of 5 to 60° with respect to the thickness direction of the thermal conductive sheet. [Prior art documents] [Patent Documents]
[0005] [Patent Document 1] Patent No. 6156337 [Overview of the project] [Problems that the invention aims to solve]
[0006] Here, the thermal conductive sheet is interposed between the heat-generating element and the heat-sinking element to exert its thermal conductivity. The pressure applied to the gap between the heat-generating element and the heat-sinking element can be as low as 0.3 MPa depending on the application. Therefore, the thermal conductive sheet needs to have low thermal resistance even when the pressure applied in the thickness direction is low. However, conventional thermal conductive sheets had room for further reduction in thermal resistance when the pressure applied in the thickness direction was low.
[0007] Therefore, the present invention aims to provide a thermally conductive sheet with low thermal resistance during low-pressure compression. [Means for solving the problem]
[0008] The inventors diligently conducted research to achieve the above objectives. As a result, the inventors newly discovered that a thermal conductive sheet containing a resin and plate-shaped boron nitride particles exhibits excellent thermal conductivity at low pressure compression when the thermal conductive sheet contains multiple voids, the resin contains a crosslinked resin, the volume fraction of plate-shaped boron nitride particles in the thermal conductive sheet is above a certain level, and when the thermal conductive sheet is compressed in the thickness direction at 0.3 MPa, the compression ratio calculated by a predetermined formula is 8.7% or higher, thus completing the present invention.
[0009] In other words, the present invention aims to advantageously solve the above problems, and the present invention is a thermal conductive sheet comprising [1] a resin and plate-shaped boron nitride particles, wherein the thermal conductive sheet comprises a plurality of voids, the resin contains a crosslinked resin, the volume fraction of the plate-shaped boron nitride particles in relation to the volume of the thermal conductive sheet is 50 volume% or more, and when the thermal conductive sheet is compressed in the thickness direction at 0.3 MPa, the compressibility calculated according to the following formula (1) is 8.7% or more. Compression rate (%)=100×[1-(T 0.3 / T0)][%]···(1) (In equation (1), T 0.3 (where T0 represents the thickness of the thermal conductive sheet when a pressure of 0.3 MPa is applied, and T0 represents the thickness of the thermal conductive sheet in an unpressurized state.) Such a thermal conductive sheet exhibits low thermal resistance and excellent thermal conductivity under low-pressure compression. The compression ratio can be measured according to the method described in the examples of this specification.
[0010] [2] Here, in the heat conductive sheet described in [1] above, it is preferable that among the plurality of voids in the heat conductive sheet, the length of the major axis when the contour of the void is approximated as an ellipse is 20% or more of the thickness of the heat conductive sheet, and that the major axis of the void is oriented at an orientation angle of 30° to 80° with respect to the main surface of the heat conductive sheet. Such a thermal conductive sheet exhibits excellent compressibility, even lower thermal resistance during low-pressure compression, and superior thermal conductivity. The length of the long axis of the void can be measured by the method described in the examples. Furthermore, the orientation angle of the long axis of the void can be measured by the method described in the examples.
[0011] [3] Furthermore, in the thermal conductive sheet described in [1] or [2] above, it is preferable that the porosity calculated according to the following formula (2) is 10% or more. Porosity (%) = 100 × (1 - Measured specific gravity of thermal conductive sheet ÷ Theoretical specific gravity of thermal conductive sheet) ... (2) Such a thermally conductive sheet exhibits excellent compressibility, low thermal resistance during low-pressure compression, and superior thermal conductivity. The porosity can be calculated according to the method described in the examples of this specification.
[0012] [4] In addition, in any of the thermal conductive sheets described in [1] to [3] above, it is preferable that the aspect ratio of the void is 8 or greater. Such a thermal conductive sheet exhibits excellent compressibility, low resistance during low-pressure compression, and superior thermal conductivity. The aspect ratio of the void can be measured by the method described in the examples.
[0013] [5] In addition, any of the thermal conductive sheets described in [1] to [4] above may further contain a plasticizer. Such thermal conductive sheets have excellent compressibility, low resistance during low-pressure compression, and even better thermal conductivity. [Effects of the Invention]
[0014] According to the present invention, a thermally conductive sheet with low thermal resistance during low-pressure compression can be provided. [Brief Description of the Drawings]
[0015] [Figure 1] It is a schematic cross-sectional view in the thickness direction of the thermally conductive sheet of the present invention according to one example. [Modes for Carrying Out the Invention]
[0016] Hereinafter, embodiments of the present invention will be described in detail. Since the thermally conductive sheet of the present invention has thermal conductivity, it can be used by being sandwiched between a heating element and a heat radiating element. For example, the thermally conductive sheet of the present invention can be used by being interposed between heating elements such as semiconductors, electronic displays, and general electronic components, and heat radiating elements such as heat sinks, heat radiating plates, and heat radiating fins, to bond these elements to each other, thereby forming an electronic device. In particular, since the thermally conductive sheet of the present invention has low thermal resistance during low-pressure compression, it can be suitably used in heat dissipation applications for high-performance semiconductors, which have been increasingly common in recent years.
[0017] (Thermally Conductive Sheet) The thermally conductive sheet of the present invention contains a resin and plate-like boron nitride particles, and also includes a plurality of voids. The resin contained in the thermally conductive sheet contains a crosslinked resin. Furthermore, in the thermally conductive sheet, the volume fraction of the plate-like boron nitride particles occupying the volume of the thermally conductive sheet is 50% by volume or more. The thermally conductive sheet of the present invention is characterized in that when the thermally conductive sheet is compressed at 0.3 MPa in the thickness direction, the compression ratio calculated according to the following formula (1) is 8.7% or more. Compression ratio (%) = 100 × [1 - (T 0.3 / T0)] [%] ··· (1) (In formula (1), T 0.3 represents the thickness of the thermally conductive sheet when a pressure of 0.3 MPa is applied, and T0 represents the thickness of the thermally conductive sheet in a non-pressurized state.) The thermal conductive sheet of the present invention, which satisfies these conditions, can exhibit high thermal conductivity even when compressed at low pressure. Furthermore, such a thermal conductive sheet also has excellent resilience due to the cross-linked structure of the resin within the sheet.
[0018] <Plate-shaped boron nitride particles> In this specification, plate-like boron nitride refers to boron nitride particles with an aspect ratio (major axis / minor axis) of 1.4 or greater. The plate-shaped boron nitride particles preferably have an aspect ratio of 10.0 or less, and more preferably 5.0 or less. It is presumed that an aspect ratio of 10.0 or less makes it easier for the plate-shaped boron nitride particles to orient well in the thickness direction within the thermal conductive sheet, thereby improving the thermal conductivity of the thermal conductive sheet in the thickness direction. Furthermore, flake-shaped boron nitride can be suitably used as the plate-shaped boron nitride. There is no particular lower limit to the aspect ratio, but it is preferably 1.1 or more. In this invention, the "aspect ratio" can be determined by observing boron nitride particles with a scanning electron microscope (SEM), measuring the maximum diameter (major axis) and the particle diameter in the direction perpendicular to the maximum diameter (minor axis) for any 50 boron nitride particles, and calculating the average value of the ratio of major axis to minor axis (major axis / minor axis). In the above, for example, if the plate-like boron nitride particles are scale-shaped, the "major axis" refers to the length in the direction of the major axis of the main surface of the scale-shaped particle, and the "minor axis" refers to the length in the direction perpendicular to the major axis of the main surface.
[0019] The volume-average particle diameter of the plate-shaped boron nitride particles is preferably 10 μm or more, preferably 20 μm or more, more preferably 30 μm or more, preferably 60 μm or less, and more preferably 50 μm or less. If the volume-average particle diameter of the plate-shaped boron nitride particles is above the lower limit, it is presumed that good heat transfer paths can be formed in the thermal conductive sheet, thereby improving the thermal conductivity of the thermal conductive sheet. On the other hand, if the volume-average particle diameter of the plate-shaped boron nitride particles is below the upper limit, a sufficiently high thickness accuracy of the thermal conductive sheet can be ensured. Furthermore, if the volume-average particle diameter of the plate-shaped boron nitride particles is within the above predetermined range, the thermal conductivity of the thermal conductive sheet can be further improved. In this invention, "volume-average particle diameter" can be measured in accordance with JIS Z8825 and represents the particle diameter at which the cumulative volume calculated from the smallest diameter side accounts for 50% of the particle size distribution (volume-based) measured by laser diffraction. Furthermore, it is known that there is virtually no discrepancy between the particle size of plate-like boron nitride particles at the material stage and the particle size at the stage where they are contained in the thermal conductive sheet after the manufacturing process. Therefore, if the particle size of plate-like boron nitride particles at the material stage is within the above range, it can be inferred that the particle size of plate-like boron nitride particles in the thermal conductive sheet will also be within the above range.
[0020] <<Content of plate-shaped boron nitride particles>> Furthermore, the content of plate-shaped boron nitride particles in the thermal conductive sheet must be 50 volume% or more, preferably 80 volume% or less, more preferably 70 volume% or less, and even more preferably 65 volume% or less, based on the volume of the thermal conductive sheet. If the content of plate-shaped boron nitride particles in the thermal conductive sheet is above the lower limit, the thermal resistance of the thermal conductive sheet can be suppressed and the thermal conductivity can be further enhanced. Also, if the content of plate-shaped boron nitride particles in the thermal conductive sheet is below the upper limit, the porosity of the thermal conductive sheet can be made appropriate and the compressibility can be further enhanced. In addition, if the content of plate-shaped boron nitride particles in the thermal conductive sheet is below the upper limit, in particular, when the thermal conductive sheet has a structure in which strips are joined in parallel to each other at a predetermined angular range with respect to the main surface, the separation of the strips of the thermal conductive sheet can be effectively suppressed and the resilience of the thermal conductive sheet can be enhanced.
[0021] Furthermore, the orientation angle of the plate-like boron nitride particles is preferably 30° to 80° with respect to the main surface of the thermal conductive sheet, similar to the long axis of the void described later. This is because it ensures thermal conductivity while also increasing compressibility. It is thought that the thermal conductivity itself increases as the orientation angle of the plate-like boron nitride particles approaches 90°, but when the thermal conductive sheet is compressed in the thickness direction and the film thickness decreases, the thermal resistance of the thermal conductive sheet itself tends to decrease. Therefore, the thermal conductivity of the thermal conductive sheet when compressed can be determined by the balance between how easily the thermal conductive sheet can be crushed and the thermal conductivity of the thermal conductive sheet when uncompressed.
[0022] <Resin> The heat conductive sheet of the present invention contains a resin, which allows for good adhesion between the heat-generating element and the heat-sinking element via the heat conductive sheet. In this specification, rubber and elastomer are included in "resin". The resin that may be included in the heat-conducting sheet of the present invention constitutes a matrix resin and also functions as a binder that binds plate-shaped boron nitride particles together. Furthermore, the resin contained in the heat-conducting sheet of the present invention contains a cross-linked resin.
[0023] <<Crosslinked resin>> The resin contained in the heat conductive sheet of the present invention contains a crosslinked resin. The crosslinked resin is a resin that has been crosslinked with a crosslinking agent. Furthermore, when the heat conductive sheet of the present invention has a structure in which strips are joined in parallel to each other within a predetermined angular range with respect to the main surface, the inclusion of a crosslinked resin as the resin causes the parallel joined strips to be crosslinked, resulting in excellent resilience.
[0024] Here, a resin that is solid at room temperature and atmospheric pressure is preferred as the crosslinked resin. In this specification, "room temperature" refers to 23°C and "atmospheric pressure" refers to 1 atm (absolute pressure).
[0025] The crosslinked resin is formed by a crosslinking reaction between a crosslinkable resin and a crosslinking agent. A crosslinking accelerator can be used in the crosslinking reaction.
[0026] [Crosslinkable resin] The crosslinkable resin is not particularly limited, and depending on the type of crosslinking agent and crosslinking accelerator, for example, solid resins and liquid resins that are liquid at room temperature and pressure can be used. In order to avoid the crosslinkable resin becoming excessively hard and losing its elasticity, it is preferable that it does not contain epoxy groups, in other words, that it is a resin other than an epoxy resin.
[0027] -A resin that is solid at room temperature and pressure- Examples of resins that are solid at room temperature and pressure include acrylic polymers such as poly(2-ethylhexyl acrylate), copolymers of acrylic acid and 2-ethylhexyl acrylate, polymethacrylic acid or its esters, and polyacrylic acid or its esters; styrene-acrylonitrile copolymer; acrylonitrile-butadiene-styrene copolymer (ABS resin); styrene-butadiene copolymer or its hydrogenated product; acrylonitrile-butadiene copolymer (nitrile rubber); styrene-butadiene block copolymer or its hydrogenated product; styrene-isoprene block copolymer or its hydrogenated product; silicone resins such as polyimide silicone resin; and fluororesins such as vinylidene fluoride-based fluororesins, tetrafluoroethylene-propylene-based fluororesins, and tetrafluoroethylene-purple orovinyl ether-based fluororesins. These may be used individually or in combination of two or more. Among these, it is preferable that the heat conductive sheet of the present invention contains a crosslinked resin, which is a crosslinked product formed using at least one of the acrylic polymer, acrylonitrile-butadiene copolymer, and styrene-butadiene copolymer.
[0028] [Liquid resin] The liquid resin is not particularly limited, but for example, liquid nitrile butadiene rubber or liquid acrylic resin can be used. These may be used individually or in combination of two or more in any ratio. The proportion of the liquid resin to the volume of the thermal conductive sheet may be 0 vol% or more, 5 vol% or more, 10 vol% or more, preferably 25 vol% or less, and may be 15 vol% or less. If the volume ratio of the liquid resin to the volume of the thermal conductive sheet is within the above range, a thermal conductive sheet with even better compressibility and resilience can be obtained.
[0029] The crosslinkable resin preferably has a glass transition temperature of -50.0°C or higher, more preferably -35.0°C or higher, even more preferably -32.0°C or higher, preferably -8.0°C or lower, more preferably -15.0°C or lower, and even more preferably -20.0°C or lower. If the glass transition temperature of the resin used as the crosslinkable resin is above the lower limit, the resilience of the resulting thermal conductive sheet can be further enhanced, resulting in even higher thermal conductivity. Furthermore, if the glass transition temperature of the resin used as the crosslinkable resin is below the upper limit, the resulting thermal conductive sheet can be given appropriate flexibility, resulting in even higher thermal conductivity.
[0030] [Crosslinking agent] The crosslinking agent is not particularly limited as long as it can crosslink with the crosslinkable resin described above, and is not limited as long as it is used as a crosslinking agent for resins. Typical crosslinking agents include sulfur-based crosslinking agents, peroxides, and amine-based crosslinking agents that crosslink the unsaturated bonds contained in the resin. These may be used individually or in combination of two or more in any ratio. In particular, when the crosslinkable resin is an acrylic polymer, it is preferable to use an amine-based crosslinking agent such as hexamethylenediamine carbamate, and when the crosslinkable resin is at least one of acrylonitrile-butadiene copolymer and styrene-butadiene copolymer, a sulfur-based crosslinking agent is preferred.
[0031] The amount of crosslinking agent is preferably 0.1 parts by mass or more, more preferably 0.2 parts by mass or more, even more preferably 0.3 parts by mass or more, preferably 5.0 parts by mass or less, and more preferably 2.5 parts by mass or less, per 100 parts by mass of crosslinkable resin. If the amount of crosslinking agent is within the above range, the formed crosslinked resin will be sufficiently crosslinked by the crosslinking agent, thereby imparting appropriate strength and elasticity to the thermal conductive sheet, improving the resilience of the thermal conductive sheet, and maintaining a good orientation structure of plate-like boron nitride particles inside the thermal conductive sheet.
[0032] [Crosslinking accelerator] The crosslinking accelerators that can be used in the crosslinking reaction between a crosslinkable resin and a crosslinking agent are not particularly limited, and guanidine-based crosslinking accelerators and sulfenamide-based crosslinking accelerators can be used. These may be used individually or in combination of two or more in any ratio. Among these, guanidine-based crosslinking accelerators are preferred.
[0033] The amount of crosslinking accelerator added is preferably 0.5 parts by mass or more, more preferably 0.7 parts by mass or more, even more preferably 1.0 part by mass or more, preferably 5.0 parts by mass or less, and more preferably 4.0 parts by mass or less, per 100 parts by mass of crosslinkable resin. If the amount of crosslinking accelerator added is within the above range, the formed crosslinked resin will be sufficiently crosslinked by the crosslinking agent, thereby imparting appropriate strength and elasticity to the thermal conductive sheet, improving the resilience of the thermal conductive sheet, and maintaining a good orientation structure of the long axes of plate-like boron nitride particles and voids inside the thermal conductive sheet.
[0034] [Percentage of cross-linked resin content] The proportion of crosslinked resin contained in the thermal conductive sheet must be 50% by volume or less, preferably 45% by volume or less, preferably 20% by volume or more, more preferably 25% by volume or more, and even more preferably 30% by volume or more, based on the volume of the thermal conductive sheet. If the proportion of crosslinked resin based on the volume of the thermal conductive sheet is above the above lower limit, such a thermal conductive sheet will have even better thermal conductivity. The amount of crosslinked resin contained in the thermal conductive sheet is usually equal to the amount of crosslinkable resin used in the manufacturing of the thermal conductive sheet.
[0035] [Other resins] The thermal conductive sheet may contain resins other than the crosslinkable resin. The other resins are not particularly limited, but include resins that do not undergo a crosslinking reaction due to the crosslinking agent and crosslinking accelerator that contribute to the crosslinking of the aforementioned crosslinkable resin.
[0036] <<Plasticizer>> The thermal conductive sheets described herein may optionally contain plasticizers. The inclusion of plasticizers in the thermal conductive sheets enhances their flexibility and compressibility. In this specification, a plasticizer refers to a substance that is liquid and fluid at room temperature and pressure, has a molecular weight of less than 10,000, and a viscosity of 200 mPa·s or more and 100 Pa·s or less when measured with a B-type viscometer at 20 rpm and 25°C. It is preferable that the plasticizer does not crosslink with the same crosslinking system as the crosslinked resin. If the plasticizer does not crosslink with the same crosslinking system as the crosslinked resin, flexibility can be imparted to the entire sheet even after the crosslinkable resin has been crosslinked during the manufacturing of the thermal conductive sheet, resulting in a thermal conductive sheet with excellent compressibility.
[0037] As plasticizers, for example, adipic acid ether ester compounds such as di(butoxyethoxyethyl) adipic acid and fatty acid esters such as sebacate esters can be used. The volume ratio of the plasticizer to the volume of the thermal conductive sheet is preferably 1% by volume or more, more preferably 5% by volume or more, even more preferably 10% by volume or more, preferably 25% by volume or less, and more preferably 15% by volume or less. If the volume ratio of plasticizer to the volume of the thermal conductive sheet is above the lower limit, flexibility is imparted to the entire sheet, resulting in a thermal conductive sheet with excellent compressibility. If the volume ratio of plasticizer to the volume of the thermal conductive sheet is below the upper limit, a thermal conductive sheet with excellent resilience can be obtained.
[0038] <Other ingredients> The thermal conductive sheet of the present invention may optionally further contain components other than those described above (hereinafter sometimes referred to as "other components"). These other components are not particularly limited as long as they can be used in the manufacture of the thermal conductive sheet, and include, for example, fibrous carbon materials; flame retardants such as red phosphorus-based flame retardants and phosphate ester-based flame retardants; plasticizers such as fatty acid ester-based plasticizers; toughness modifiers such as urethane acrylates; hygroscopic agents such as calcium oxide and magnesium oxide; adhesion enhancers such as silane coupling agents, titanium coupling agents, and acid anhydrides; wettability enhancers such as nonionic surfactants and fluorine-based surfactants; ion trapping agents such as inorganic ion exchangers; and foaming agents such as anti-aging agents and sulfonyl hydrazide compounds. These may be blended in the required amounts depending on the application. The upper limit of the content of these other components is not particularly limited, but it may be, for example, 10% by volume or less, preferably 5% by volume or less, relative to the total volume of the thermal conductive sheet. The thermal conductive sheet may also be free of other components. In addition, while the foaming agent described in the example above is mostly removed from the thermal conductive sheet during manufacturing due to foaming, a very small amount of residue (for example, less than 0.5% by volume based on the total volume of the thermal conductive sheet) may remain in the thermal conductive sheet.
[0039] <Structure of a thermal conductive sheet> In the heat-conducting sheet of the present invention, it is preferable that at least a portion of the above-mentioned plurality of voids has a major axis length of 20% or more of the thickness of the heat-conducting sheet when the contour is approximated as an ellipse. Furthermore, it is preferable that the major axis, which is 20% or more of the thickness of the heat-conducting sheet, is oriented at an orientation angle of 30° to 80° with respect to the main surface of the heat-conducting sheet.
[0040] Furthermore, the aspect ratio of voids in the thermal conductive sheet whose long axis length is 20% or more of the thickness of the thermal conductive sheet is preferably 8 or more, more preferably 9 or more, even more preferably 10 or more, preferably 50 or less, more preferably 40 or less, and even more preferably 35 or less. If the aspect ratio of the predetermined voids is above the lower limit, excellent compressibility can be achieved. Also, if the aspect ratio of the predetermined voids is below the upper limit, excellent thermal conductivity can be achieved because there are no excessively large voids.
[0041] Furthermore, it is preferable that the thermal conductive sheet of the present invention has a structure in which the above-mentioned plurality of voids are uniformly dispersed within the main surface of the thermal conductive sheet. If the plurality of voids are uniformly dispersed within the main surface in this way, the compressibility and thermal conductivity of the thermal conductive sheet can be further improved in a well-balanced manner. It is also presumed that at least some of the plurality of voids have a so-called continuous cell structure, which is formed by the interconnection of voids originating from the particles of the plurality of foaming agents. It is thought that such a continuous cell structure can be efficiently produced by carrying out a "crosslinking reaction step in which the laminate is heated under pressure to perform crosslinking and foaming reactions" in the manufacturing method described in one example later. It is also thought that such a continuous cell structure can form voids whose long axes are oriented at a predetermined orientation angle with respect to the main surface of the thermal conductive sheet.
[0042] Figure 1 schematically shows a cross-section in the thickness direction of an example of the heat conductive sheet of the present invention that satisfies the above-described specific structure. Figure 1 partially shows a cross-section obtained by cutting the heat conductive sheet 1 perpendicular to the main surface, i.e., in a direction coinciding with the thickness direction. The heat conductive sheet 1 contains a resin 10 and plate-shaped boron nitride particles (shape not shown). The plate-shaped boron nitride particles are represented by their major axis 11 (dashed line), and their shape is omitted for clarity. Furthermore, the heat conductive sheet 1 contains a plurality of voids 12 shown as approximations of an ellipse, and at least a portion of these voids 12 have a major axis LA length of 20% or more of the distance between the first main surface A and the second main surface B of the heat conductive sheet 1, i.e., the thickness of the heat conductive sheet 1. Furthermore, it is preferable that the long axis LA, whose length is 20% or more of the thickness of the heat conductive sheet 1, is oriented at an orientation angle of 30° to 80° with respect to the first main surface A and the second main surface B of the heat conductive sheet 1 (approximately 60° in Figure 1). In the embodiment shown in Figure 1, all of the illustrated voids 12 have a long axis LA whose length is 20% or more of the thickness of the heat conductive sheet 1, and all of these LAs are oriented at an orientation angle of approximately 60° with respect to the first main surface A and the second main surface B of the heat conductive sheet 1. Although not shown, the heat conductive sheet 1 may also contain unintended voids that occur during kneading. Such unintended voids are often very small spherical voids.
[0043] Here, the major axes of multiple voids, whose major axis length is 20% or more of the thickness of the thermal conductive sheet, are preferably oriented at an orientation angle of 30° to 80°, as described above. Furthermore, it is more preferable that the major axes are oriented at an orientation angle of 35° to 75°, and even more preferable that they are oriented at an orientation angle of 45° to 70°. If the predetermined major axes of the voids within the thermal conductive sheet are inclined at an orientation angle within the above range, compressibility and thermal conductivity can be further improved in a more balanced manner. In addition, the orientation angle of the plate-shaped boron nitride particles with respect to the main surface of the thermal conductive sheet is preferably 30° to 80°, preferably within the range of 35° to 75°, and more preferably within the range of 45° to 70°. If the orientation angle of the plate-shaped boron nitride particles with respect to the main surface of the thermal conductive sheet is within the above range, the compressibility of the thermal conductive sheet and thermal conductivity at low pressure can be further improved.
[0044] (Properties of thermal conductive sheets) <Porosity> The porosity of the thermal conductive sheet is a value calculated according to the following formula (2). Porosity (%) = 100 × (1 - Measured specific gravity of thermal conductive sheet ÷ Theoretical specific gravity of thermal conductive sheet) ... (2) The porosity is preferably 10% or more, more preferably 15% or more, more preferably 20% or more, preferably 40% or less, more preferably 35% or less, and even more preferably 30% or less. If the porosity is above the lower limit, compressibility can be further enhanced. Also, if the porosity is below the upper limit, excellent thermal conductivity can be achieved.
[0045] <Compression ratio> The heat conductive sheet of the present invention has a thickness of T when pressurized at 0.3 MPa in the thickness direction. 0.3Assuming that T0 is the thickness of the thermal conductive sheet before pressurization, the compressibility of the thermal conductive sheet calculated by the following formula (1) must be 8.7% or more, more preferably 9.5% or more, even more preferably 11.0% or more, and particularly preferably 11.5% or more. The upper limit of the compressibility is not particularly limited and may be, for example, 20.0% or less, and from the viewpoint of further improving thermal conductivity, it is more preferably 15.5% or less. Compression rate (%)=100×[1-(T 0. 3 / T0)][%]···(1) If the compressibility value is above the lower limit, the thermal conductive sheet can be compressed even at relatively low pressure, exhibiting excellent adhesion to the heat-generating and heat-dissipating elements, as well as superior ability to conform to uneven surfaces. Furthermore, if the compressibility value is below the upper limit, the thermal conductive sheet possesses appropriate strength and excellent durability. The compressibility can be controlled according to the composition and manufacturing method of the thermal conductive sheet. The compressibility is a value that can be measured for a 1mm thick thermal conductive sheet using the method described in the examples.
[0046] <Recovery Rate> Furthermore, the heat conductive sheet of the present invention, after being pressurized at 0.9 MPa in the thickness direction, unloaded, and allowed to recover for 3 minutes, preferably has a recovery rate of 85% or more, and more preferably 90% or more, calculated based on the following formula (3). Recovery rate (%) = (Thickness of thermal conductive sheet after recovery) ÷ (Thickness of thermal conductive sheet before pressurization) ... (3) If the recovery rate is greater than or equal to the lower limit mentioned above, the material can conform better to the component. The upper limit of the recovery rate is not particularly limited and may be, for example, 100%. The recovery rate can be controlled according to the composition and manufacturing method of the thermal conductive sheet. Furthermore, the recovery rate is a value that can be measured for a 1mm thick thermal conductive sheet using the method described in the examples.
[0047] <Thermal resistance> The thermal conductive sheet of the present invention preferably has a thermal resistance value of 1.20°C / W or less, and more preferably 1.18°C / W or less, under each condition in which a pressure of 0.3 MPa is applied in the thickness direction at a sample temperature of 50°C. If the thermal resistance value is below the above upper limit, the thermal conductivity of the thermal conductive sheet can be improved. The lower limit of the thermal resistance value is not particularly limited, but it can usually be 0.10°C / W or more. The thermal resistance value can be controlled according to the composition and manufacturing method of the thermal conductive sheet. Furthermore, the thermal resistance is a value that can be measured for a 1 mm thick thermal conductive sheet using the method described in the examples.
[0048] <Thermal conductivity> The thermal conductivity of the thermal conductive sheet in the thickness direction is preferably 8.0 W / m·K or higher, and more preferably 9.0 W / m·K or higher. Furthermore, there is no particular upper limit to the value of the thermal conductivity of the thermal conductive sheet in the thickness direction, but for example, it is 35 W / m·K or lower. The thermal conductivity in the thickness direction of the thermal conductive sheet can be adjusted by the type and proportion of materials and components contained in the thermal conductive sheet, as well as the manufacturing method and conditions of the thermal conductive sheet. Furthermore, the thermal conductivity is a value that can be measured for a 1 mm thick thermal conductive sheet using the method described in the examples.
[0049] <Thickness of the thermal conductive sheet> The thickness of the thermal conductive sheet of the present invention is not particularly limited, but is preferably 100 μm or more, more preferably 300 μm or more, more preferably 500 μm or more, preferably 5000 μm or less, more preferably 3000 μm or less, and even more preferably 1500 μm or less. If the thickness of the thermal conductive sheet is above the lower limit, the compressibility of the thermal conductive sheet can be further increased. If the thickness of the thermal conductive sheet is below the upper limit, the thermal conductivity in the thickness direction of the thermal conductive sheet can be increased.
[0050] (Method for manufacturing thermal conductive sheets) The heat conductive sheet of the present invention can be efficiently manufactured by manufacturing method 1, which includes: (A) a pre-heat conductive sheet molding step of pressurizing a composition containing a crosslinkable resin, plate-shaped boron nitride particles, a crosslinking agent, and a foaming agent to form a sheet to obtain a pre-heat conductive sheet; (B) a laminate formation step of stacking multiple pre-heat conductive sheets in the thickness direction, or folding or winding the pre-heat conductive sheets to obtain a laminate; (C) a crosslinking reaction step of heating the laminate under pressure to carry out crosslinking and foaming reactions; and (D) a slicing step of slicing the laminate at an angle of 20° to 60° with respect to the stacking direction to obtain a heat conductive sheet. The manufacturing method may optionally further include steps other than those described in (A) to (D) above.
[0051] Alternatively, the thermal conductive sheet of the present invention can also be manufactured by another manufacturing method 2 different from manufacturing method 1. For example, a structure corresponding to the laminate obtained through steps (A) to (C) of manufacturing method 1 can be manufactured by a method involving the orientation of plate-shaped boron nitride particles. Specifically, a structure can be obtained by molding a composition containing at least resin and plate-shaped boron nitride particles by mold molding or the like, applying an orientation operation using a magnetic field, and then curing the resin, following the method described in Japanese Patent No. 6846641. Furthermore, a thermal conductive sheet can be obtained by slicing the structure at an angle of 20° to 60° with respect to the orientation direction, similar to step (D) of manufacturing method 1.
[0052] The following describes an example of the manufacturing method 1 described above for a thermal conductive sheet, but the present invention is not limited thereto.
[0053] <(A) Pre-heat conductive sheet molding process> In the pre-heat-conducting sheet molding process, a composition containing a crosslinkable resin, plate-shaped boron nitride particles, a crosslinking agent, and a foaming agent is pressurized and molded into a sheet to obtain a pre-heat-conducting sheet.
[0054] <<Composition>> The above composition comprises a resin containing a crosslinkable resin, plate-shaped boron nitride particles, a crosslinking agent, and a foaming agent. The above composition may further contain a crosslinking accelerator. Furthermore, the above composition may further contain components other than the resin, plate-shaped boron nitride particles, crosslinking agent, foaming agent, and crosslinking accelerator (other components).
[0055] [resin] Here, the resin contained in the composition contains a crosslinkable resin and optionally contains a resin other than the crosslinkable resin. As the crosslinkable resin, for example, the crosslinkable resin that can be used to form the crosslinkable resin described above in the "Thermal Conductive Sheet" section can be used in the proportion described above. The amount of resin blended in the composition corresponds to the blending range described for the "resin content ratio" contained in the thermal conductive sheet described above. Also, the amount of crosslinkable resin blended in the resin corresponds to the blending range described for the "crosslinkable resin content ratio" contained in the thermal conductive sheet described above. As the resin other than the crosslinkable resin, for example, other resins that can be included in the resin described above in the "Thermal Conductive Sheet" section can be used.
[0056] [Plate-shaped boron nitride particles] As plate-shaped boron nitride particles, for example, the plate-shaped boron nitride particles described above in the "Thermal Conductive Sheet" section can be used in the proportions described above.
[0057] [Crosslinking agent] As the crosslinking agent, the crosslinking agent that can be used to form the crosslinked resin described above in the "Thermal Conductive Sheet" section can be used in the proportions described above.
[0058] [Foaming agent] As blowing agents, various blowing agents that decompose upon heating to generate gas can be used. Furthermore, blowing aids that lower the decomposition temperature of the blowing agent and promote its decomposition may be combined with the blowing agent. Specific examples of blowing agents include, for example, one or more chemical blowing agents such as azo compounds like azodicarbonamide (ADCA) and azobisisobutyronitrile, nitroso compounds like N,N'-dinitrosopentamethylenetetramine (DPT), and sulfonyl hydrazide compounds like p-toluenesulfonyl hydrazide and 4,4'-oxybis(benzenesulfonyl hydrazide) (OBSH); and gaseous blowing agents such as chlorofluorocarbons (CFCs), carbon dioxide, water, pentane, and volatile hydrocarbon compounds, as well as microcapsules containing these. The proportion of the foaming agent is preferably 5% by mass or more, and preferably 15% by mass or less, relative to the resin contained in the composition. If the proportion of the foaming agent is above the lower limit, the foaming reaction can be carried out well, making the resulting thermal conductive sheet even more compressible. If the proportion of the foaming agent is below the upper limit, the strength and resilience of the resulting thermal conductive sheet can be improved.
[0059] The foaming temperature depends on the type of foaming agent, but it is desirable to have a temperature between 80°C and 220°C. In particular, a temperature between 150°C and 200°C is desirable.
[0060] [Effervescent agent] As mentioned above, various foaming agents can be used as foaming aids that lower the decomposition temperature of the foaming agent they are combined with, thereby promoting its decomposition. For example, urea (H2NCONH2)-based foaming agents can be used as foaming aids when combined with ADCA.
[0061] The proportion of the foaming agent can be arbitrarily set depending on the type of foaming agent to be combined, but it is preferably 1% by mass or more, and preferably 15% by mass or less, relative to the resin contained in the composition.
[0062] As a foaming agent, it is particularly preferable to use ADCA in combination with a urea-based foaming agent, or to use OBSH alone. Of these, it is more preferable to use OBSH alone.
[0063] [Crosslinking promoter] As a crosslinking accelerator, the one described above in the "Thermal Conductive Sheet" section can be used in the proportion described above.
[0064] [Other ingredients] Other components that may be included in the composition include the other components that may be included in the thermal conductive sheet as described above in the "Thermal Conductive Sheet" section.
[0065] [Preparation of composition] The composition is not particularly limited and can be prepared by mixing the above-mentioned components. The mixing of the above-mentioned components can be carried out using known mixing equipment such as a kneader, mixer (e.g., Henschel mixer, Hobart mixer, high-speed mixer), twin-shaft kneader, or rolls, without any particular limitations. The mixing may also be carried out in the presence of a solvent such as ethyl acetate. The resin may be dissolved or dispersed in the solvent beforehand to form a resin solution, which can then be mixed with boron nitride particles, a crosslinking agent, a foaming agent, and optionally added crosslinking accelerators and other components. The mixing time can be, for example, 5 minutes to 60 minutes. The mixing temperature can be, for example, 5°C to 150°C.
[0066] <<Formation of the composition>> The composition prepared as described above can be optionally degassed and crushed, and then pressed to form a sheet. A sheet formed by pressing the composition in this way can be used as a pre-heat-conducting sheet. If a solvent is used during mixing, it is preferable to remove the solvent before forming the sheet. For example, if degassing is performed using vacuum degassing, the solvent can be removed at the same time as degassing.
[0067] Here, the composition can be formed into a sheet using known forming methods such as press forming, rolling forming, or extrusion forming, without any particular limitations, as long as the forming method involves the application of pressure. In particular, it is preferable to form the composition into a sheet by rolling forming (primary processing), and it is even more preferable to form it into a sheet by predetermined roll forming, in which the composition is passed between a first roll and a second roll having a faster peripheral speed than the first roll. The peripheral speed ratio of the second roll to the first roll ("peripheral speed of the second roll" / "peripheral speed of the first roll") is preferably 1.03 / 1 or more and 2 / 1 or less. The distance between the first roll and the second roll may be, for example, 1 mm or more and 3 mm or less.
[0068] <<Pre-heat conductive sheet>> Furthermore, in a pre-heat-conductive sheet formed by pressurizing the composition into a sheet, the plate-like boron nitride particles are mainly oriented in the in-plane direction, and it is presumed that the in-plane thermal conductivity of the pre-heat-conductive sheet is particularly improved.
[0069] <(B) Laminate formation process> In the laminate formation process, multiple pre-heat conductive sheets obtained in the pre-heat conductive sheet molding process are laminated in the thickness direction, or the pre-heat conductive sheets are folded or wound to obtain a laminate in which multiple pre-heat conductive sheets containing resin, plate-shaped boron nitride particles, a crosslinking agent, and a foaming agent are formed in the thickness direction. Here, the formation of the laminate by folding the pre-heat conductive sheets is not particularly limited and can be done by folding the pre-heat conductive sheets to a certain width using a folding machine. Furthermore, the formation of the laminate by winding the pre-heat conductive sheets is not particularly limited and can be done by winding the pre-heat conductive sheets around an axis parallel to the short or long direction of the pre-heat conductive sheets. Furthermore, the formation of the laminate by lamination of pre-heat conductive sheets can be done using a lamination apparatus without particular limitations.
[0070] Furthermore, in laminates obtained by stacking, folding, or winding pre-heat-conductive sheets, it is presumed that the plate-like boron nitride particles are oriented in a direction approximately perpendicular to the stacking direction.
[0071] <(C) Crosslinking reaction process> In the crosslinking reaction step, it is preferable to heat the laminate obtained in the laminate formation step (hereinafter sometimes referred to as the first laminate) and apply pressure (secondary pressure) isotropically in the lamination direction or relative to the laminate to form a second laminate. By heating the laminate and advancing the crosslinking reaction, the crosslinkable resin undergoes a crosslinking reaction to form a crosslinked resin, thereby improving the resilience of the manufactured thermal conductive sheet. In addition, simultaneously with the crosslinking reaction, the foaming agent undergoes a foaming reaction to generate voids, further improving the compressibility of the thermal conductive sheet.
[0072] Here, the pressure applied to the laminate in the stacking direction can be between 0.05 MPa and 0.90 MPa. Alternatively, hydrostatic pressing can be performed using equipment such as an autoclave. The pressure for hydrostatic pressing is preferably in the range of 0.1 MPa and 0.9 MPa.
[0073] Furthermore, the heating temperature of the laminate is not particularly limited, but is preferably above 140°C, more preferably above 150°C, even more preferably above 170°C, preferably below 210°C, and more preferably below 190°C. If the heating temperature is above the lower limit, the crosslinking reaction and foaming reaction can be carried out well, thereby improving the resilience of the manufactured thermal conductive sheet and creating voids within the thermal conductive sheet, further improving the compressibility of the thermal conductive sheet. If the heating temperature is below the upper limit, the deterioration of the resin constituting the thermal conductive sheet can be suppressed. Here, the foaming ratio in the crosslinking reaction step is preferably 1.05 times or more, more preferably 1.10 times or more, preferably 1.50 times or less, and more preferably 1.30 times or less. If the foaming ratio is above the lower limit, the compressibility of the thermal conductive sheet can be further improved. Also, if the foaming ratio is below the upper limit, the resilience of the thermal conductive sheet can be further improved.
[0074] Furthermore, the heating time of the laminate is not particularly limited, but for example, it may be between 30 minutes and 6 hours. If the heating time is above the lower limit, the crosslinking reaction and foaming reaction can be carried out well, thereby improving the resilience of the manufactured thermal conductive sheet and creating voids within the thermal conductive sheet, further increasing the compressibility of the thermal conductive sheet. On the other hand, if the heating time is below the upper limit, the crosslinking reaction can be suppressed to prevent it from progressing excessively, and the flexibility of the thermal conductive sheet can be maintained well, resulting in further increasing the compressibility of the thermal conductive sheet.
[0075] Furthermore, in the second laminate obtained through the crosslinking reaction process, it is presumed that the crosslinkable resin has been crosslinked to become a crosslinked resin, and that the plate-like boron nitride particles are oriented in a direction approximately perpendicular to the lamination direction.
[0076] <(D) Slicing process> In the slicing process, the laminate that has undergone the crosslinking and foaming reactions in the crosslinking reaction process is sliced at an angle of 20° to 60° with respect to the lamination direction to obtain a heat conductive sheet made of sliced pieces of the laminate. The method of slicing the laminate is not particularly limited and includes, for example, the multi-blade method, laser processing method, water jet method, knife processing method, etc. The cutting tool used when slicing the laminate is not particularly limited and can be a slicing member having a smooth surface with a slit and a blade portion protruding from the slit (for example, a plane or slicer with a sharp blade).
[0077] Furthermore, from the viewpoint of improving the thermal conductivity of the thermal conductive sheet, the slicing angle of the laminate is preferably 10° or more, more preferably 15° or more, even more preferably 20° or more, preferably 60° or less, more preferably 55° or less, and even more preferably 50° or less with respect to the lamination direction.The thermal conductive sheet obtained through such a slicing process may have a structure in which strips containing resin and plate-like boron nitride particles are bonded in parallel at an angle within the above range with respect to the thickness direction of the thermal conductive sheet.
[0078] Furthermore, the thermal conductive sheet obtained in this manner contains multiple voids due to the foaming of the foaming agent, and a cross-linked resin is formed, resulting in excellent compressibility and thermal conductivity (especially thermal conductivity under low-pressure compression). [Examples]
[0079] The present invention will be described in detail below based on examples, but the present invention is not limited to these examples. In the following description, "%" and "parts" used to express quantities refer to mass unless otherwise specified. In each example and each comparative example, various attributes were measured or evaluated by the following methods.
[0080] (Measurement and evaluation of the physical properties of thermal conductive sheets) <Orientation angle of plate-like boron nitride> The orientation angle of the plate-like boron nitride in the thermal conductive sheets obtained in each example and comparative example was determined by observing the cross-section of the thermal conductive sheet, which was cut into a regular octagon, using a scanning electron microscope (SEM, Hitachi High-Technologies, "SU-3500") at a magnification that captured the entire sheet from top to bottom. The magnification used was 100x. If the filler could not be distinguished due to resolution limitations, the magnification could be increased. In this case, evaluation was performed at three locations in the thickness direction of the sheet: top, middle, and bottom, and the largest value among the three locations was taken as the orientation angle of the plate-like boron nitride in the sheet. Specifically, 50 lines were drawn along the long axis of the plate-like boron nitride in the cross-section, and the average angle of the long axis relative to the surface of the thermal conductive sheet was calculated. If the angle was 90° or greater, a supplementary angle was used. This was performed on eight surfaces, and the largest value among the eight surfaces was taken as the orientation angle of the plate-like boron nitride in the thermal conductive sheet.
[0081] <Orientation angle and aspect ratio of the void> The voids in the cross-section where the orientation angle of the plate-like boron nitride was maximized, as determined during the measurement of the orientation angle of the plate-like boron nitride, were evaluated. Specifically, the average aspect ratio, orientation angle, and length of the major axis of the voids, observable at the same magnification as above, were evaluated. In calculating the average aspect ratio of the voids, the contours of the voids included in the "cross-section with the maximum angle" of the thermal conductive sheet were first approximated as ellipses, and the major and minor axes were set for each ellipse. Then, voids whose major axis length was 20% or more of the thickness of the thermal conductive sheet were determined to be voids caused by the foaming agent and were subject to evaluation. Voids with a length of less than 20% of the thickness of the thermal conductive sheet were determined to be unintended voids generated during mixing. Furthermore, the aspect ratio of the voids was calculated by dividing the length of the major axis of the voids determined to be evaluated above by the length of the minor axis. Ten voids were selected in descending order from the largest aspect ratio, and the average aspect ratio was obtained. For all examples and comparative examples, ten voids were selected, and the average aspect ratio was calculated. The angle of the major axis of the selected voids was then calculated in the same way as for boron nitride particles. Furthermore, when evaluating the orientation angle and aspect ratio of voids in a thermal conductive sheet with fewer than 10 voids in its cross-section, it is sufficient to target a thermal conductive sheet with 5 or more voids in its cross-section, select these 5 voids as the measurement targets, and evaluate them in the same manner as described above.
[0082] <Thickness of the thermal conductive sheet> The thickness of the thermal conductive sheets obtained in the examples and comparative examples was measured using a thickness gauge (Mitutoyo Corporation, product name "Digimatic Indicator ID-C112XBS"). Ten measurements were taken, and the arithmetic mean of the obtained thickness measurement data was taken as the thickness (μm) of the thermal conductive sheet in question.
[0083] <Thermal conductivity> [Thermal diffusivity α in the thickness direction] The thermal diffusivity of the thermal conductive sheet was measured using a thermal diffusion / thermal conductivity measuring device (ai-PhaseMobile 1u, manufactured by iPhase Co., Ltd.) in accordance with the provisions of ISO22007-3. [Specific heat at constant pressure Cp] A differential scanning calorimeter (Rigaku, product name "DSC8230") was used to measure the specific heat at 25°C under a heating condition of 10°C / min. [Specific gravity ρ (density)] The measurement was performed using an automatic hydrometer (manufactured by Toyo Seiki Co., Ltd., product name "DENSIMETER-H"). Then, each measurement value is expressed using the following formula (I): λ = α × Cp × ρ···(I) By substituting these values, the thermal conductivity λ (W / m·K) in the thickness direction of the thermal conductive sheet at 25°C was determined.
[0084] <Theoretical specific gravity and porosity> For each example and comparative example, the theoretical specific gravity was calculated from the specific gravity of the raw materials and their proportions for the heat-conducting sheets produced. From the calculated theoretical specific gravity and measured specific gravity, the following formula (2): Porosity (%) = 100 × (1 - Measured specific gravity of thermal conductive sheet ÷ Theoretical specific gravity of thermal conductive sheet) ... (2) The void ratio (%) was calculated using the method described above.
[0085] <Thickness, thermal resistance, and compressibility> The thickness, thermal resistance, and compressibility of the thermal conductive sheets produced in each example and comparative example were measured using a thermal resistance tester (manufactured by Hitachi Technology & Services, Ltd., product name "Resin Material Thermal Resistance Measuring Device"). Here, a thermal conductive sheet cut into a roughly square 1 cm square was used as a sample, and the thickness value (T0) of the thermal conductive sheet before pressurization was measured. Then, at a sample temperature of 50°C, the thickness and thermal resistance value (°C / W) of the thermal conductive sheet were measured under pressures of 0.3 MPa and 0.9 MPa in the thickness direction, respectively. Furthermore, from the viewpoint of more clearly expressing the degree of improvement in the thermal resistance of the sheet when other conditions are changed using the same type of resin, the improvement rate of thermal resistance relative to Comparative Example 1 was also calculated for Examples 1 to 5 and Comparative Examples 2 to 3. In addition, the improvement rate of thermal resistance relative to Comparative Example 4 was also calculated for Examples 6 to 10. Furthermore, the thickness of the above sample before pressurization T0 and the thickness of the above sample after applying a pressure of 0.3 MPa are given as T. 0.3and T0 and T 0.3 were used to calculate the compressibility (%) according to the following formula (1). Compressibility (%) = 100 × [1 - (T 0.3 / T0)][%] ··· (1) Further, after the measurement, the pressure applied to the sample was further increased to 0.9 MPa, and the thickness of the sample at this time was defined as T 0.9 , then the load was removed, and after 3 minutes had elapsed, the thickness of the restored thermally conductive sheet was measured with a film thickness meter, and the recovery rate was calculated based on the following formula (3). Recovery rate (%) = (Thickness T of the thermally conductive sheet after restoration 0.9 ) ÷ (Thickness T0 of the thermally conductive sheet before pressurization) ··· (3)
[0086] (Production Example 1) <Preparation of Composition> As the resin, acrylic rubber which is a solid acrylic resin at normal temperature and normal pressure (crosslinkable solid acrylic resin, manufactured by Nippon Zeon Co., Ltd., trade name "Nipol (registered trademark) AR-12", glass transition temperature: -30.3°C, specific gravity: 1.10 g / cm 3 ) 180 parts, and di(butoxyethoxyethyl) adipate as a plasticizer (adipic acid ether ester plasticizer, trade name "Adeka Sizer RS-107", manufactured by ADEKA Corporation, specific gravity: 1.02 g / cm 340.0 parts of ) and 460 parts of hexagonal boron nitride (h-BN) (manufactured by Dandong Chemical Engineering, trade name "HSPD50", aspect ratio: 1.5, specific gravity: 2.23, volume average particle diameter 50 μm), which is plate-like (flaky) boron nitride as boron nitride particles, were kneaded at a temperature of 120°C for 20 minutes using a pressurized kneader (manufactured by Nippon Spindle) to obtain the composition. To the obtained composition, 2.7 parts of Nocrack 224S (2,2,4-trimethyl-1,2-dihydroquinoline polymer) as an antioxidant, 0.9 parts of Diak #1 (hexamethylenediamine carbamate, manufactured by Chemours) as a crosslinking agent, 3.6 parts of Noxellar DT (di-o-tolylguanidine) as a crosslinking accelerator, and 9.0 parts of a foaming agent (manufactured by Eiwa Chemical Industries, Ltd., trade name "Neocervon 1000S"), 4,4-oxybis(benzenesulfonyl hydrazide; median diameter 14 μm; dp = 160°C) were added, and the mixture was kneaded at 80°C for 5 minutes to obtain the composition.
[0087] (Manufacturing example 2) The composition was obtained in the same manner as in Production Example 1, except that a foaming agent was not included in the <Preparation of Composition>.
[0088] (Manufacturing Example 3) The composition was obtained in the same manner as in Production Example 1, except that the composition was changed as shown in Table 1 in the <Preparation of Composition> section (in particular, the volume fraction of plate-like boron nitride particles was set to 40% by volume).
[0089] (Manufacturing example 4) <Preparation of Composition (Nitrile Resin Composition)> The resin consists of 56 parts of liquid nitrile butadiene rubber (manufactured by Nippon Zeon, trade name "Nipole 1312", specific gravity: 1.0) which is liquid at room temperature and pressure, and a crosslinkable resin, nitrile butadiene rubber (NBR) (manufactured by Nippon Zeon Co., Ltd., trade name "Nipol (registered trademark) 3335", specific gravity: 1.00 g / cm³) which is solid at room temperature and pressure. 3) 130 copies, and as a plasticizer, di(butoxyethoxyethyl) adipate (adipate ether ester plasticizer, product name "ADEKA Sizer RS-107", manufactured by ADEKA, specific gravity: 1.02 g / cm³ 3 45 parts of ) and 520 parts of hexagonal boron nitride (h-BN) (manufactured by Dandong Chemical Engineering, trade name "HSPD50", aspect ratio: 1.5, specific gravity: 2.23, volume average particle diameter 50 μm), which is plate-like (flaky) boron nitride as boron nitride particles, were kneaded at a temperature of 120°C for 20 minutes using a pressurized kneader (manufactured by Nippon Spindle) to obtain the composition. To the obtained composition, 2.8 parts of Nocrack 224S (2,2,4-trimethyl-1,2-dihydroquinoline polymer) as an antioxidant, 2.8 parts of dicumyl peroxide (product name "Perkmyl D40") as a crosslinking agent, and 9.3 parts of a blowing agent (manufactured by Eiwa Chemical Industries, Ltd., product name "Neocervon 1000S"), 4,4-oxybis(benzenesulfonyl hydrazide; median diameter 14 μm; dp = 160°C) were added, and the mixture was kneaded at 80°C for 5 minutes to obtain the composition.
[0090] (Manufacturing example 5) The composition (nitrile resin composition) was prepared in the same manner as in Production Example 4, except that the composition was changed as shown in Table 1 (in particular, the volume fraction of plate-like boron nitride particles was set to 60% by volume).
[0091] (Example 1) <Preheat conductive sheet molding process> 500g of the composition obtained in Production Example 1 was rolled into a sheet using a first roll and a second roll under the following conditions: a gap of 1mm between the first and second rolls, a roll temperature of 25°C, a sheet discharge speed (outer circumference speed of the first roll) of 2m / min, and an outer circumference speed ratio of the second roll to the first roll (second roll / first roll): 1.15 / 1. The rolling process was repeated while keeping the sheet conveying direction the same. A total of 10 rolling processes were performed to obtain a pre-heat-conductive sheet with a thickness of 1mm.
[0092] <Laminate formation process> Next, the obtained pre-heat conductive sheets were cut into 50mm x 50mm sections, and 50 sheets were stacked in the thickness direction to obtain a laminate with a height of approximately 50mm.
[0093] <Crosslinking reaction process (crosslinked laminate formation process)> The resulting laminate was caramel-wrapped in release PET (polyethylene terephthalate), sealed with tape, and vacuum-packed in PET retort packaging. To hydrostatic press this, it was placed in an autoclave (Haneuda Iron Works, small autoclave "DANDELION") and heated and pressurized for 30 minutes at a temperature of 170°C with a pressure of 0.8 MPa (absolute pressure) applied from all directions, allowing the crosslinking and foaming reactions to proceed and obtaining a crosslinked laminate. Furthermore, the expansion ratio was calculated by dividing the height of the resulting cross-linked laminate by the height of the original laminate.
[0094] <Slicing process> While pressing the laminated surface of the cross-linked laminate obtained above with a pressure of 0.3 MPa, a woodworking slicer (manufactured by Marunaka Iron Works Co., Ltd., product name "Super Mecha S Super Finishing Planer") was used to slice the laminate at an angle of approximately 10° with respect to the lamination direction, thereby obtaining a secondary sheet (thermal conductive sheet) measuring 50 mm in length, 50 mm in width, and 1000 μm in thickness. The thermal conductive sheet is composed of strips that are joined in parallel at an 80° angle to the main surface of the thermal conductive sheet. The obtained thermal conductive sheets were subjected to various measurements and evaluations according to the above procedure. The results are shown in Table 2.
[0095] (Examples 2-4) The procedure was the same as in Example 1, except that the slicing angle in the <slicing process> was changed to approximately 20° (Example 2), 30° (Example 3), and 40° (Example 4) with respect to the stacking direction, so that the orientation angle of the voids with respect to the main surface of the sheet was 70° (Example 2), 60° (Example 3), and 50° (Example 4), respectively. The results are shown in Table 2.
[0096] (Example 5) The <crosslinking reaction process (crosslinked laminate formation process)> was carried out as described below, and the procedure was the same as in Example 1, except that the slicing angle in the <slicing process> was changed to 20° with respect to the lamination direction. The results are shown in Table 2. <Crosslinking reaction process (crosslinked laminate formation process)> The resulting laminate was placed in a mold that allowed both ends in the lamination direction of the laminate to be fixed with jigs (metal plates), and the mold was placed in an autoclave (Hanyuuda Iron Works, small autoclave "DANDELION"). In the autoclave, the crosslinking and foaming reactions were carried out for 30 minutes under heating and pressurizing treatment at a temperature of 180°C and a pressure of 0.8 MPa (absolute pressure) applied from all directions, to obtain a crosslinked laminate. The original laminate had a height of 5 cm, and the distance between the metal plates was set to 6.2 cm to allow the crosslinking and foaming reactions to proceed. After cooling, the height of the crosslinked laminate was measured and found to be 6 cm due to a slight shrinkage of the laminate during cooling. The foaming ratio was calculated by dividing the height of the obtained crosslinked laminate by the height of the original laminate.
[0097] (Comparative Example 1) The procedure was the same as in Example 1, except that the slicing angle in the <slicing process> was set to 0° with respect to the stacking direction, i.e., slicing was performed along the stacking direction. The results are shown in Table 2.
[0098] (Comparative Example 2) The composition used was that of Production Example 2 (without foaming agent), and the procedure was carried out in the same manner as in Example 1, except that the slicing angle in the <slicing process> was changed to 20° with respect to the stacking direction (i.e., the orientation angle of the voids became 70° with respect to the main surface). The results are shown in Table 2.
[0099] (Comparative Example 3) The composition used was that of Production Example 3 (with a volume fraction of plate-like boron nitride particles of 40 vol%), and the procedure was carried out in the same manner as in Example 1, except that the slicing angle in the <slicing process> was changed to 20° with respect to the stacking direction (i.e., the orientation angle of the voids became 70° with respect to the main surface). The results are shown in Table 2.
[0100] (Example 6) The procedure was carried out in the same manner as in Example 1, except that the nitrile resin composition according to Production Example 4 was used as the composition. The results are shown in Table 3.
[0101] (Examples 7-9) The procedure was the same as in Example 6, except that the slicing angle in the <slicing process> was changed to approximately 20° (Example 7), 30° (Example 8), and 40° (Example 9) with respect to the stacking direction, so that the orientation angle of the voids with respect to the main surface of the sheet was 70° (Example 7), 60° (Example 8), and 50° (Example 9), respectively. The results are shown in Table 3.
[0102] (Example 10) The procedure was carried out in the same manner as in Example 6, except that the nitrile resin composition according to Production Example 5 was used as the composition. The results are shown in Table 3.
[0103] (Comparative Example 4) The procedure was the same as in Example 6, except that the slicing angle in the <slicing process> was set to 0° with respect to the stacking direction, i.e., slicing was performed along the stacking direction. The results are shown in Table 3.
[0104] [Table 1]
[0105] [Table 2]
[0106] [Table 3]
[0107] Tables 2-3 show that the thermal conductive sheets of Examples 1-9, which include a crosslinked resin and plate-like boron nitride particles, have low thermal resistance even when compressed at low pressures such as 0.3 MPa. The thermal conductive sheets contain multiple voids, the resin contains a crosslinked resin, the volume fraction of plate-like boron nitride particles in the thermal conductive sheet is above a certain level, and when the thermal conductive sheet is compressed in the thickness direction at 0.3 MPa, the compression ratio calculated by a predetermined formula is 8.7% or higher. On the other hand, the thermal conductive sheets according to Comparative Examples 1, 2, and 4, whose compressibility calculated using the prescribed formula is less than 8.7%, and the thermal conductive sheet according to Comparative Example 3, which has a low content of plate-like boron nitride particles, are significantly inferior in terms of thermal resistance during low-pressure compression. [Industrial applicability]
[0108] According to the present invention, it is possible to provide a thermally conductive sheet with low thermal resistance during low-pressure compression. [Explanation of Symbols]
[0109] 1. Thermal conductive sheet 10 resin 11 Long axis of plate-like boron nitride particles 12 void A First principal surface B Second principal surface
Claims
1. A thermal conductive sheet comprising a resin and plate-shaped boron nitride particles, The aforementioned heat conductive sheet includes a plurality of voids, The aforementioned resin contains a crosslinked resin, The volume fraction of the plate-shaped boron nitride particles in relation to the volume of the thermal conductive sheet is 50 volume% or more. When the aforementioned thermal conductive sheet is compressed in the thickness direction at 0.3 MPa, the compression ratio calculated according to the following formula (1) is 8.7% or more. Compression rate (%) = 100 × [1 - (T) 0.3 / T 0 )] [%]... (1) (In equation (1), T 0.3 The thickness of the thermal conductive sheet when a pressure of 0.3 MPa is applied is T 0 (These terms refer to the thickness of the heat conductive sheet in an unpressurized state.) Thermal conductive sheet.
2. The thermal conductive sheet according to claim 1, wherein, among the plurality of voids in the thermal conductive sheet, the length of the major axis of a void whose contour is approximated as an ellipse is 20% or more of the thickness of the thermal conductive sheet, the major axis of the void is oriented at an orientation angle of 30° to 80° with respect to the main surface of the thermal conductive sheet.
3. The thermal conductive sheet according to claim 1, wherein the porosity calculated according to the following formula (2) is 10% or more. Porosity (%) = 100 × (1 - measured specific gravity of the thermal conductive sheet ÷ theoretical specific gravity of the thermal conductive sheet) ... (2)
4. The thermal conductive sheet according to claim 1, wherein the aspect ratio of the void is 8 or more.
5. The thermal conductive sheet according to any one of claims 1 to 4, wherein the thermal conductive sheet further contains a plasticizer.
Citation Information
Patent Citations
Focusing mechanism of exposing optical device
JP1986056337A